Comparison of Serum Spec fPL™ and 1, 2‐o‐Dilauryl‐Rac‐Glycero‐3‐Glutaric Acid‐(6′‐Methylresorufin) Ester Assay in 60 Cats Using Standardized Assessment of Pancreatic Histology. (10th March 2016) - Oppliger, S.; Hilbe, M.; Hartnack, S.; Zini, E.; Reusch, C.E.; Kook, P.H.
Abstract : Background: Feline pancreas‐specific lipase (Spec fPL) is considered a useful test for the antemortem diagnosis of pancreatitis in cats. A recent study found good agreement between the results of the Spec fPL and catalytic 1, 2‐ o ‐dilauryl‐rac‐glycero‐3‐glutaric acid‐(6′‐methylresorufin) ester (DGGR) lipase assay. Prospective studies evaluating their sensitivity and specificity are lacking. Objectives: To compare the results of the Spec fPL and the DGGR assays with a standardized histologic assessment of the pancreas. Animals: Sixty client‐owned cats presented for necropsy. Methods: Prospective study: Spec fPL concentrations and serum DGGR lipase activity were measured from the same blood sample. The pancreas was removed within 3 hours after euthanasia; serial transverse sections were made every 0.5 cm throughout the entire pancreas and reviewed using a histologic grading scheme. Sensitivity and specificity for the Spec fPL and DGGR assay results were determined. Results: The sensitivity and specificity for the Spec fPL assay (cutoff value ≥5.4 μg/L) was 42.1 [95% confidence interval (95% CI), 29.4–55.9%] and 100% (95% CI, 31.0–100.0%). The sensitivity and specificity for the DGGR assay (cutoff value >26 U/L) was 36.8 (95% CI, 24.7–50.7%) and 100% (95% CI, 31.0–100.0%). When lymphocytic inflammation up to 10% of a section was considered normal, the sensitivity and specificity for Spec fPL assay (cutoff value ≥5.4 μg/L) was 61.1 (95% CI, 36.1–81.7%) and 69.0% (95% CI, 52.8–81.9%) and the sensitivity and specificity for the DGGR assay (cutoff value >26 U/L) was 66.7 (95% CI, 41.2–85.6%) and 78.6% (95% CI, 62.8–89.2%). Conclusions and Clinical Importance: Both lipase assays performed similarly well, but their agreement with histologic pancreatic inflammation was limited.